Effectiveness of Digital Systems and Learning Models in Online Learning for Students from Underprivileged Families - Veronica Yulisna Sinukaban; Damai Linda Gea Vetrycia; Nizwardi Jalinus; Hansi Efendi (Edumaspul: Jurnal Pendidikan, 2022)
Online learning has become an alternative learning system during the COVID-19 pandemic, but in reality, online learning raises many problems in its implementation. Online learning is not only viewed negatively by some people, but also shows a wide digital divide in society, especially the economically disadvantaged, which ultimately results in educational inequality. Poor students and those who live in rural areas find it difficult to access online learning due to the absence of ICT facilities and difficulty getting internet signals. Education in Indonesia, which has embraced the neoliberal paradigm of competition since the beginning, eventually results in unfair competition in online learning due to the digital divide. This research aims to find out the extent of the digital divide and the education model in online learning implemented at the State Vocational High School (SMK) 1 Beringin, which then results in inequality in competition between students. This study also wants to see the resolution of economic disparities, and evaluate the competition system in education that is always discriminatory and only benefits some people, then rethinking a more humane education model.